Molecular cloning, expression and biochemical characterization of hemoglobin gene from ark shell Scapharca broughtonii. Issue 78 (July 2018) - Zhao, Qing; Wu, Biao; Liu, Zhihong; Sun, Xiujun; Zhou, Liqing; Yang, Aiguo; Zhang, Gaowei
Abstract: Hemoglobin, the main component of haemolymph, is widely distributed in animals. Although its important oxygen transport functions has been extensively reported, studies on the immune function of hemoglobin in mollusc are few. Research on immune of hemoglobin of ark shell Scapharca broughtonii attracted more and more attention due to its ownership of erythrocyte comparing with many other shellfish. In this study, the hemoglobin cDNA of S. broughtonii was cloned by EST and RACE methods (named as SbHb ). Sequence analysis revealed that the cDNA was 946 bp in length, including an open reading frame (ORF) of 459 bp which encoded a polypeptide of 152 amino acid residues, and a 5′-untranslated region (UTR) of 313 bp, a 3′-UTR of 174 bp. Sequence and homology analysis showed that the SbHb shared similarity with that of other related species. The mRNA expression profiles of SbHb in tested tissues analyzed by quantitative real-time PCR (qRT-PCR) revealed that the mRNA of SbHb could be all detected in foot, gill, mantle, adductor muscle, haemocytes and hepatopancreas, and the highest level was found in the haemocytes, which is 163.2 times higher than that in adductor muscle. Vibrio anguillarum stimulation and hypoxia treatment both had significant impact on the expression of SbHb, which showed the same trends as increasing first to the highest at 16 h after treatment and then followed by declining. Recombinant protein of SbHb (rSbHb) was successfully obtained by prokaryotic expression, and further function analysis indicated obviously that the rSbHb had very strong phenoloxidase-like activity (PO-like activity) and it could remarkably inhibit growth of gram-negative bacteria V. anguillarum . All the data suggested that the SbHb plays a significant role in the process of antibacterial and anoxia tolerance reaction in S. broughtonii, providing the evidence that SbHb is a key immune factor. Highlights: Full length cDNA of hemoglobin in S. broughtonii ( SbHb ) and recombinant protein SbHb are obtained. Biochemical analysis indcates that SbHb is involved in the acute phase response.